Optoelectronic simulation and optimization of all perovskites tandem solar cells employing electrodeposited copper oxide as hole transport layer - Vishwas D. Patel; Dhritiman Gupta (Scientific Reports)
Abstract Tandem solar cells are highly promising photovoltaic device that can potentially beat the maximum power conversion efficiency achieved so far in a single junction silicon solar cell by mitigating both the thermalization and transmission losses commonly encountered in a single junction solar cell. Among several different components of a tandem solar cell, hole-transport layer (HTL) plays an important role. Present day state of the art HTL layers are limited in number and sometimes highly expensive. In this work, we explore the feasibility of using electrodeposited Cu2O and mixed phase (Cu2O + CuO) Cu–O film as HTL in all-perovskite tandem solar cells and a detail optical, compositional and morphological analysis was performed. To access its performance as HTL in tandem devices, here we adapted an optoelectronic simulation approach using SCAPS-1D software tool and transfer matrix simulation routine where the parameters were either measured experimentally or carefully optimized to replicate the performance under realistic testing conditions. Photovoltaic parameters for single-junction cells with Cu2O-HTL was found to be less sensitive on the electron affinity of the Cu2O as opposed to that of Cu–O in a Cu–O-HTL based single junction cells. The highest efficiency predicted in our simulation is 24.95% in a 2-terminal tandem device with Cu2O-HTL and electron affinity of 3.8 eV whereas with similar device architecture, in a 4-terminal tandem device, the highest efficiency can reach upto 35%.